Sosialisasi Safety Riding Dalam Mengurangi Kecelakaan Lalu Lintas Kendaraan Roda Dua : Socialization of Safety Riding in Reducing Two-Wheeled Vehicle Traffic Accidents - Made Chandra (Police Studies Review, 2019)
This research is motivated by the high number of traffic accidents of two-wheeled vehicles that occur in Purwakarta Regency. This traffic problem caused the disruption of the traffic jams which was the responsibility of the traffic unit at the Purwakarta Police. Satlantas Polres Purwakarta is making preventive efforts to reduce the number of two-wheeled vehicle traffic accidents through the Dikyasa Unit by carrying out community education activities in the field of traffic, one of which is the socialization of safety riding, but if it is related to the facts in the field, the number of traffic accidents is still high, it is necessary to evaluate the implementation. socialization of safety riding. In this study, the authors used a qualitative approach, using the type of field research, as well as data collection techniques by conducting interviews, observing, and reviewing documents. Research sources that are used as references relating to the implementation of safety riding socialization. The theory used is management theory and communication theory. The concept used is the concept of a two-wheeled vehicle traffic accident, the concept of safety riding and the concept of Kamseltibcar immediately. The results showed that the implementation of the socialization of safety riding required proper management and methods to support the socialization activities. In addition, the communication that occurs in the socialization of safety riding is very important to ensure the delivery of traffic messages to the public which can be seen from the embedded aspects of traffic discipline in the community of Purwakarta Regency. The conclusion of this research is that the implementation of safety riding socialization carried out by the Unit Dikyasa Satlantas Purwakarta Police has not been maximized, this can be seen from the lack of supporting facilities for activities and the lack of innovation in conveying safety riding socialization messages.